Dispersion reduction of the analyses data for more reliable fragility curves of selected electric substations equipment - Mohammadpour, Saman; Hosseini, Mahmood (Springer, 2022)
High dispersion of data, either obtained by field investigations, or created by time history analyses (THA), for developing fragility curves (FCs), results in remarkable uncertainty in seismic risk evaluation. Regarding the lack of studies on uncertainty reduction of FCs of electric power equipment, this paper presents three means for reducing this dispersion: (1) using spectral acceleration at fundamental period of the system, S-a(T-1), instead of peak ground acceleration (PGA) as the intensity measure (IM), (2) using S-a(T-1) + S-a(T-2), as the IM, and (3) using a set of scenario earthquakes for THA instead of randomly chosen accelerograms. First, a brief history of FCs development for electric power equipment is presented, followed by a short review of the studies on improvement of fragility functions. Then, comparison of the mentioned methods for two key structures of electric substations, a post insulator (PI) and a current transformer (CT) is done. For the PI, first a set of randomly chosen accelerograms was employed, once using PGA, and once more S-a(T-1) as the IM, and then a set of scenario-based records, with the same IMs. For the CT, first PGA, then S-a(T-1) and finally S-a(T-1) + S-a(T-2) were used as the IM. Results show that using scenario-compatible records leads to more consistent data for developing the FCs, and that this consistency gets better and much better, respectively, by using S-a(T-1) and S-a(T-1) + S-a(T-2) as the IM. It is suggested that for very high frequency systems, such as PI, S-a(T-1) is used, while for moderate- and low-frequency systems, such as CT, S-a(T-1) + S-a(T-2) is used.
Keywords: Intensity measure; Spectral acceleration at the system's fundamental period; Time history analysis; Post insulator; Current transformer; Scenario-compatible earthquakes